2006
DOI: 10.1097/00006982-200603000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Toxicity of the Kenalog Vehicle (Benzyl Alcohol) in Rabbits

Abstract: Benzyl alcohol at concentrations modestly higher than what is present in commercial Kenalog is toxic to the rabbit eye. This has been shown in other organ systems. If commercial preserved Kenalog is to be used clinically, decanting the supernatant or using other means to remove the benzyl alcohol may be considered, especially if a volume of >0.1 mL of solution is used. We hypothesize that the noninfectious inflammation seen clinically after Kenalog injection is due to the presence of a toxic preservative at un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(65 citation statements)
references
References 36 publications
2
59
1
3
Order By: Relevance
“…With regard to the retinal haemorrage, it has been previously suggested that it may be caused by the vehicle used in the preparation of intravitreal TA (26).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the retinal haemorrage, it has been previously suggested that it may be caused by the vehicle used in the preparation of intravitreal TA (26).…”
Section: Discussionmentioning
confidence: 99%
“…63 Foi proposto, recentemente, que o preservativo álcool benzílico presente no veículo da TA seria responsável pela indução de lesões retinianas. 64,18 (Figura 11e Tabela 1)…”
Section: Corantes Vitais Para O Vítreounclassified
“…The safety of TA to the retina has been demonstrated by several in-vitro and in-vivo studies (8) ; intravitreal injection of TA in high concentration (up to 30mg) yielded no relevant retina toxicity, while our investigation disclosed no damage to the retinal tissue after subretinal preservative-free TA-injection in rabbits (69) . It has been recently proposed that the preservative benzyl alcohol present in TA-vehicle induce most retinal damage and nowadays the crystals deposition of TA is considered the gold standard substance for posterior hyaloid and vitreous base identification ( figure 10 and table 1) (19,70) .…”
Section: Triancinolone Acetonidementioning
confidence: 99%